Effect of smoking on vitamin C and MDA: a cross sectional comparative study - Kubihal, Chandrashekar V.; Naik, Hemalatha D. (International Journal of Research in Medical Sciences, 2019)
Background: Plasma gets exposed to the gases present in the smoke of the cigarette which leads to peroxidation. The ascorbic acid present in the body gets oxidized there is danger of derangement of lipid profile. The measure of malondialdehyde which is formed in lipid peroxidation reaction is indicative of oxidative stress. Oxidative stress seen among the smokers has been attributed to high MDA levels. Objective was to study the effect of smoking on vitamin C and MDA. Methods: Present study was cross sectional study. Two groups of subjects were compared. Out of 100 study subjects, 25 were non smokers and were kept in one group. Remaining 75 were smokers. These two groups were compared to find out how the smoking habit affects the MDA as well as vitamin C levels among them. Results: The levels of MDA were more in smokers compared to those who did not smoke and this difference was significant. The levels of vitamin C were less in smokers compared to those who did not smoke and this difference was significant (p<0.05). It was found that the MDA levels were significantly more among all degrees of smokers. It was less in smokers with mild degree compared to smokers with heavy or moderate degree. Level of vitamin C was more in non smokers compared to smokers. Mild degree of smokers had better levels of vitamin C compared to moderate degree of smokers. Conclusions: Smoking affects the vitamin C levels and MDA levels in the human body.